2020
DOI: 10.3390/plants9070870
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of β-Carboline Profile of Banisteriopsis caapi and Ayahuasca, a Plant and a Brew with Neuropharmacological Potential

Abstract: Ayahuasca is a psychoactive infusion with a large pharmacological application normally prepared with Banisteriopsis caapi, which contains the monoamine oxidase inhibitors β-carbolines, and Psichotria virids, which contains the serotonin receptor agonist N,N dimethyltryptamine (DMT). The objectives of this study were to investigate the chemical profile of B. caapi and of ayahuasca collected in various Brazilian regions. In total, 176 plant lianas, of which 159 B. caapi and 33 ayahuasca samples were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…In samples prepared by traditional ritualistic procedures, which consists in the decoction of P. viridis leaves together with the stems of B. caapi, alkaloid variation reached a tenfold magnitude [13]. For other hand, great variability of B. caapi, with at least 30 different varieties described and cataloged, which have a direct relationship with different levels of alkaloids found in Ayahuasca preparations, aside from various plant proportion used by the different groups [5,18] was also reported.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In samples prepared by traditional ritualistic procedures, which consists in the decoction of P. viridis leaves together with the stems of B. caapi, alkaloid variation reached a tenfold magnitude [13]. For other hand, great variability of B. caapi, with at least 30 different varieties described and cataloged, which have a direct relationship with different levels of alkaloids found in Ayahuasca preparations, aside from various plant proportion used by the different groups [5,18] was also reported.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 94%
“…This approach was reported by Miranda et al [15] for P. viridis, the species that contributes with DMT, but in this study the authors did not report the alkaloid content in the tea. Another factor that influences secondary plant metabolism is the genetic diversity within the species, well described for the species used in the Ayahuasca beverage and for other medicinal species [18,21]. To ensure a safe use of Ayahuasca in countries outside the geographical area of naturally occurring plants (Europe and North America), a strategy would be to provide inputs for the preparation of Ayahuasca in loco at these destinations.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…Some other plants containing DMT such as Psychotria viridis or Mimosa tenuiflora (M. tenuiflora) are added to the decoction to increase its psychoactive properties [18,28,30]. Depending on the origin and development of the plants used in the preparation of ayahuasca beverages, the chemical composition may vary, both qualitatively and quantitatively [10].…”
Section: Plants Used To Prepare Ayahuasca Decoctionmentioning
confidence: 99%
“…The decoction is traditionally prepared by cooking the bark or crushed stems of the liana Banisteriopsis caapi (contains β-carbolines) alone or in combination with other plants, most commonly leaves of the shrub Psychotria viridis (contains N,N-dimethyltryptamine) [9,10]. The tea itself has a bitter taste and is not pleasant to drink [11].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have demonstrated the structural chemical similarity between the neurotransmitter 5-HT and DMT, which justifies its psychodysleptic effect on the central nervous system (CNS). The chemical structures of the main alkaloids present in the ayahuasca beverage, specifically, the DMT extracted from the leaves and the main β-carbolines (HRM, HRL and THH) extracted from the vine, are all represented in Figure 3 7,51 . Ayahuasca works as an agonist of the serotonergic system, as the DMT present in the drink is similar to 5-HT.…”
Section: Jonas Frederico Passed Away Onmentioning
confidence: 99%